Physicochemical properties and gel-forming ability changes of duck myofibrillar protein induced by hydroxyl radical oxidizing systems - Zhu, Xueshen; Shi, Xiandong; Liu, Shaohua; Gu, Ying; Liu, Junya; Fu, Qingquan; Wang, Renlei (Frontiers in Nutrition, 2022)
This paper focus on the changes of physicochemical properties and gel-forming ability of duck myofibrillar proteins (DMPs) induced using hydroxyl radical oxidizing systems. DMPs were firstly extracted and then oxidized at various H2O2 concentrations (0, 4, 8, and 12 mmol/L) using Fenton reagent (Fe3+-Vc-H2O2) to generate hydroxyl radicals, and the effects of hydroxyl radical oxidation on the physicochemical changes and heat-induced gel-forming capacity of DMPs were analyzed. We observed clear increases in the carbonyl content (p < 0.05) and surface hydrophobicity of DMPs with increasing of H2O2 concentrations (0–12 mmol/L). In contrast, the free thiol content (p < 0.05) and water retention ability of DMPs decreased with increasing H2O2 concentrations (0–12 mmol/L). These physicochemical changes suggested that high concentrations of hydroxyl radicals significantly altered the biochemical structure of DMPs, which was not conducive to the formation of a gel mesh structure. Furthermore, the gel properties were reduced based on the significant decrease in the water holding capacity (p < 0.05) and increased transformation of immobilized water of the heat-induced gel to free water (p < 0.05). With the increase of H2O2 concentrations, secondary structure of proteins analysis results indicated α-helix content decreased significantly (p < 0.05), however, random coil content increased (p < 0.05). And more cross-linked myosin heavy chains were detected at higher H2O2 concentrations groups through immunoblot analysis (p < 0.05). Therefore, as H2O2 concentrations increased, the gel mesh structure became loose and porous, and the storage modulus and loss modulus values also decreased during heating. These results demonstrate that excessive oxidation led to explicit cross-linking of DMPs, which negatively affected the gel-forming ability of DMPs. Hence, when processing duck meat products, the oxidation level of meat gel products should be controlled, or suitable antioxidants should be added.